An in vitro study comparing a peripherally inserted central catheter to a conventional central venous catheter: no difference in static and dynamic pressure transmission - Gregg Bethene L (BMC Anesthesiology, 2010)
Abstract Background Early goal directed therapy improves survival in patients with septic shock. Central venous pressure (CVP) monitoring is essential to guide adequate resuscitation. Use of peripherally inserted central catheters (PICC) is increasing, but little data exists comparing a PICC to a conventional CVP catheter. We studied the accuracy of a novel PICC to transmit static and dynamic pressures in vitro. Methods We designed a device to generate controlled pressures via a column of water allowing simultaneous measurements from a PICC and a standard triple lumen catheter. Digital transducers were used to obtain all pressure readings. Measurements of static pressures over a physiologic range were recorded using 5Fr and 6Fr dual lumen PICCs. Additionally, random repetitive pressure pulses were applied to the column of water to simulate physiologic intravascular pressure variations. The resultant PICC and control waveforms were recorded simultaneously. Results Six-hundred thirty measurements were made using the 5 Fr and 6 Fr PICCs. The average bias determined by Bland-Altman plot was 0.043 mmHg for 5 Fr PICC and 0.023 mmHg for 6 Fr PICC with a difference range of 1.0 to -1.0. The correlation coefficient for both catheters was 1.0 (p-value < 0.001). Dynamic pressure waveforms plotted simultaneously between PICC and control revealed equal peaks and troughs. Conclusion In vitro, no static or dynamic pressure differences were found between the PICC and a conventional CVP catheter. Clinical studies are required to assess whether the novel PICC has bedside equivalence to conventional catheters when measuring central venous pressures.